Desafios na articulação entre professoras de um centro de atendimento educacional especializado e escola regular para oferta de tecnologia assistiva - Lopes, Andressa (2019)
The study focused on the specialized educational service developed in a Specialized Educational Assistance Center (CAEE) regarding the availability of assistive technology and the articulation of these resources with the common class. The general objective was to propose and implement articulation actions between the teacher of the CAEE with teachers of the regular school to offer Assistive Technology resources. The research was carried out in a Special Education institution that includes a Specialized Educational Assistance Center (CAEE) and a regular municipal school in a large city in the interior of the State of São Paulo. The method adopted was a qualitative approach with a collaborative research design. Data collection was performed through the following procedures and divided into two stages: the first one was given in the context of the CAEE with the teacher to identify the use of TA resources, with the application of interview script and observation in the room CAEE, as well as the development of a training course for the use and implementation of these resources. Five meetings were held with the teacher and their subsequent evaluation. The second stage was given to the regular school in which an interview script was carried out with the participants, observation in the common room and the proposal to try to articulate among the teachers through meetings, the first and the intermediate being carried out in a way and the process of attempted articulation carried out at a distance through the use of the WhatsApp application. Aimed at the evaluation of this process, a final semi-structured interview with each participant and the application of a Likert Scale questionnaire was performed. The analysis of the data obtained was done through the elaboration of categories of analysis with the purpose of listing the information obtained through the collection instruments used. Through the analysis of the interviews and observations made in the context of the CAEE and in the common class, the absence of TA resources was verified, which required a training course for the CAEE teacher, whose purpose was to subsidize the articulation with regular school teachers. The results indicated that this course was evaluated positively by the teacher of the CAEE, being this process considered important in the work developed with PAEE in the promotion of the autonomy and functionality of this public. It was also verified the inexistence of the articulation of the pedagogical work carried out by the teachers, even though there was recognition by the teachers about the importance of this process. It was also identified that even though the attempt was made to articulate through the WhatsApp, the interactions were limited and did not allow the articulation among the teachers for the implementation of TA resources in the common class. The data indicate the need to guarantee systematized spaces within the working day of these professionals that allow them to act in an articulated manner aiming at the construction of teaching and learning processes that contribute to the inclusion of the PAEE students.